Pengaruh Budaya Organisasi Dan Kompetensi Pedagogik Terhadap Kinerja Guru - Windi Matsuko Danasasmita (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2018)
In managing the organization, there must be an appropriate strategy to regulate the workers to work as a team. The primary goal is achieving the optimum goal. Likewise, the existing organization at school must implement the proper strategies to produce the excellent teachers’ performance. The organizational culture and teachers’ competence influence their performance in an organization. This study aims to determine the impact of organizational culture and pedagogical competence on teachers’ performance. This study examined a population of teachers in a high school in Bandung. The data analysis technique of this study is path analysis. The results reveal that there is an influence of organizational culture and pedagogical competence on teachers’ performance. This finding indicates a conducive organizational culture and adequate pedagogical competence improve the teachers’ performance.